Effects of four non-invasive stimulations on swallowing function and quality of life of stroke patients—a network meta-analysis - Xinyu Lin; Haojie Li; Xie Wu; Rui Huang (Frontiers in Human Neuroscience, 2025)
BackgroundStroke is a sudden neurological disorder that causes severe neurological damage mainly due to lack of oxygen to brain cells as a result of interruption of blood flow to the brain. Dysphagia is a common problem in stroke patients, interfering with diet and nutrition and possibly leading to complications. About 50–80% of stroke patients experience dysphagia in the acute phase, which may lead to serious consequences such as aspiration and pneumonia. Therefore, improving swallowing function is essential to enhance patients’ quality of life (QoL). Traditional rehab methods are limited, but non-invasive stimulation is safer and improves swallowing function through various mechanisms: pharyngeal electrical stimulation (PES) boosts cortical excitability and plasticity by stimulating pharyngeal nerves; neuro-muscular electrical stimulation (NmeS) enhances infrahyoid muscle strength and mobility with low-frequency pulses; repetitive transcranial magnetic stimulation (rTMS) promotes motor cortex remodeling; transcranial direct current stimulation (tDCS) increases neural activity in swallowing-related regions. These techniques are safe, easy to use, and show great potential for clinical application, needing further study.MethodsSix databases were systematically searched, and 17 randomized controlled trials with 788 stroke patients were finally included. The outcome indicators were swallowing function and QoL related indicators. Net meta-analysis was performed using Stata 17.0 to assess the relative effectiveness of each combined intervention and to test the consistency of direct and indirect evidence.ResultsFor swallowing function, rTMS [SMD = 5.10, 95% CI (3.20, 7.01), p < 0.0001, SUCRA = 87.3] showed the best results. For QoL, NmeS [SMD = 3.51, 95% CI (0.54, 6.47), p < 0.0001, SUCRA = 79.3] shows all its unique advantages.ConclusionrTMS can effectively improve the swallowing function of stroke patients, while NmeS has the best effect in improving the QoL.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024603146